Concise guide to information literacy - Lanning, Scott; Gerrity, Caitlin (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2022)
"This book is designed to help librarians lead the instruction of information literacy, a transferable and essential skill for students to navigate a tsunami of information, to sort fact from opinion and opinion from propaganda"--Provided by publisher.